Pengaruh pengetahuan perpajakan, ketegasan sanksi perpajakan dan kesadaran wajib pajak terhadap kepatuhan wajib pajak pada UMKM di Kabupaten Kepulauan Sangihe - Antameng, Elfira; Sondakh , Jullie J.; Mintalangi , Syermi (Yayasan Widyantara Nawasena Raharja, 2024)
The objective of this research is to determine the influence of tax knowledge, strictness of tax sanctions, and taxpayer awareness on taxpayer compliance among MSMEs in Sangihe Islands Regency. This research employs a quantitative methodology with a descriptive approach. A questionnaire was distributed to 30 respondents from MSME actors to collect the data. The data was analysed using validity, reliability and hypothesis testing with the multiple linear regression method. The results of the research clearly show that tax knowledge and the strictness of tax sanctions have a positive and significant influence on taxpayer compliance, while taxpayer awareness does not. This research makes a significant contribution to the development of tax literature and provides clear recommendations for tax authorities to improve tax education and awareness strategies to increase taxpayer compliance in the MSME sector. The results of this research can help increase state revenues through better taxpayer compliance.